Use of proximal humerus internal locking system plate in proximal humerus fractures and its relation with the functional outcome - G. S., Prasanna Kumar; Mane, Akash V.; Yadav, Amit Kumar; Harsoor, Abhishek; Manna, Jithsen (International Journal of Research in Orthopaedics, 2019)
Background: Proximal humerus fractures are the fractures occurs at or proximal to the surgical neck of the humerus, which accounts for 7% of all fractures and 80% of all humeral fractures. Now a days most of these fractures are managed with internal fixation because of better availability of anatomical plates. The aim was to assess the functional outcome and complications of proximal humerus fractures treated with proximal humerus internal locking system (PHILOS). Methods: This is a prospective study of 30 patients with two, three, and four parts proximal humerus fractures treated with proximal humerus internal locking sysyem from 2016 to 2018 with 25 to 80 years of age in a tertiary care hospital. Functional outcome is assessed by using constant murley shoulder scoring system. Results: Functional outcome as per constant score, 10 patients (33%) got excellent outcome, 06 patients (20%) got very good outcome, 07 patients got (23%) good outcome, 05 patients got (17%) fair outcome and 02 patients got (07%) poor outcome. Complications observed were superficial infections, implant failure and axillary nerve neuropraxia. Conclusions: Open reduction and internal fixation by using PHILOS is the ideal method in treating displaced proximal humerus fractures mainly in two and three part proximal humerus fractures which provides stable fixation and less complications.